The Implementation of Skimming and Scanning in Teaching Reading at the SMP N 1 Ngrampal Sragen in 2015/2016 Academic Year - Winisuda, Rouzyta Adila; , Drs. Djoko Srijono, M.Hum (2016)
Reading is an important skill in foreign language learning. Students are expected to be competent and to develop reading skill in both formal and informal situation. However, based on the writer's observation, there was a low motivation in studying English, the students were passive in learning English and they did not have self-confidence in reading English. The writer thought that the students also need new and creative media to increase their motivation and grades. In this case, skimming and scanning techniques are the kind of method that can solve the problem. So it could be a solution to solve this problem. This research describes skimming and scanning techniques for teaching reading in SMP Negeri 1 Ngrampal, Sragen. The location of study is in SMP Negeri 1 Ngrampal, Sragen. This research is conducted in 2015/2016 academic year, started from January to April 2016. The object of study is teaching reading skills through skimming and scanning in SMP Negeri 1 Ngrampal, Sragen. Based on the research finding, it can be said that skimming and scanning technique is effective to teach students reading skill, because skimming and scanning technique provided higher thinking and do not make the student feel bored with the reading activity. Besides it, skimming and scanning technique allowed students to think what their idea to the teachers' question or topic, and they can pair with their close friend to discussion the topic, they try to draw conclusion or result from that topic and the term share, refers to the result of discussion must be shared in front of all their friends, it can be done by representative one of them. There are some conclusions related to this study, those are: The students' score of reading skill after being taught by using skimming and scanning technique is good because the mean of the total score of students is (81.2). There is any significant difference by which T-count (7.507) is bigger than T-table (2.021) of first grade students at SMP N 1 Ngrampal Sragen in reading achievement before and after they are taught by using skimming and scanning technique in the class. Based on the explanation above, it means that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. So, the using skimming and scanning technique can improve the students' reading skill in SMP Negeri 1 Ngrampal Sragen.